2009
DOI: 10.1186/1471-2105-10-s1-s33
|View full text |Cite
|
Sign up to set email alerts
|

A structural interpretation of the effect of GC-content on efficiency of RNA interference

Abstract: BackgroundRNA interference (RNAi) mediated by small interfering RNAs (siRNAs) or short hairpin RNAs (shRNAs) has become a powerful technique for eukaryotic gene knockdown. siRNA GC-content negatively correlates with RNAi efficiency, and it is of interest to have a convincing mechanistic interpretation of this observation. We here examine this issue by considering the secondary structures for both the target messenger RNA (mRNA) and the siRNA guide strand.ResultsBy analyzing a unique homogeneous data set of 101… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(66 citation statements)
references
References 39 publications
(55 reference statements)
5
60
1
Order By: Relevance
“…This finding suggested that the free energies of amiRNAs might be not the main factor that determines the resistance level of transgenic plants. This is consistent with other studies that demonstrated a lack of correlation between amiRNA (or siRNA) activity and DG (Chan et al 2009;Song et al 2014;Zhang et al 2013).…”
Section: Discussionsupporting
confidence: 94%
“…This finding suggested that the free energies of amiRNAs might be not the main factor that determines the resistance level of transgenic plants. This is consistent with other studies that demonstrated a lack of correlation between amiRNA (or siRNA) activity and DG (Chan et al 2009;Song et al 2014;Zhang et al 2013).…”
Section: Discussionsupporting
confidence: 94%
“…GC content has a rare relationship with replication timing in human genome (38). GC content also have an effect on RNAi, because it is highly correlated to RNAi target site accessibility and negatively correlated with RNAi activity (39).…”
Section: Gc Contentmentioning
confidence: 99%
“…siRNA with GC content within the range of 31.6% -57.9%, is usually recommended due to its negative correlation between GC-content and RNAi activity. 44 Four predicted consensus siRNA have found within the range of recommended GC content. The free energy of folding is a significant parameter that illustrates the stability of designed siRNA.…”
Section: Resultsmentioning
confidence: 99%